Comparative Study of Immune Reaction Against Bacterial Infection From Transcriptome Analysis - Maekawa, Shun; Wang, Pei-Chi; Chen, Shih-Chu (Frontiers in Immunology, 2019)
Transcriptome analysis is a powerful tool that enables a deep understanding of complicated physiological pathways, including immune responses. RNA sequencing (RNA-Seq)-based transcriptome analysis and various bioinformatics tools have also been used to study non-model animals, including aquaculture species for which reference genomes are not available. Rapid developments in these techniques have not only accelerated investigations into the process of pathogenic infection and defense strategies in fish, but also used to identify immunity-related genes in fish. These findings will contribute to fish immunotherapy for the prevention and treatment of bacterial infections through the design of more specific and effective immune stimulants, adjuvants and vaccines. Until now, there has been little information regarding the universality and diversity of immune reactions against pathogenic infection in fish. Therefore, one of the aims of this paper is to introduce the RNA-Seq technique for examination of immune responses in pathogen-infected fish. This review also aims to highlight comparative studies of immune responses against bacteria, based on our previous findings in largemouth bass (Micropterus salmoides) against Nocardia seriolae, grey mullet (Mugil cephalus) against Lactococcus garvieae, orange-spotted grouper (Epinephelus coioides) against Vibrio harveyi, and koi carp (Cyprinus carpio) against Aeromonas sobria, using RNA-seq techniques. We demonstrated that only 39 differentially expressed genes (DEGs) were present in all species. However, the number of specific DEGs in each species was relatively higher than that of common DEGs; 493 DEGs in largemouth bass against N. seriolae, 819 DEGs in mullets against L. garvieae, 909 in groupers against V. harveyi, and 1471 in carps against A. sobria. The DEGs in different fish species were also representative of specific immune-related pathways. The results of this study will enhance our understanding of the immune responses of fish, and will aid in the development of effective vaccines, therapies, and disease-resistant strains.